Social interactions in dementia: perceptions of current situation and opportunities - Hanna L. Knecht; Francisca S. Rodriguez (BMC Geriatrics)
Abstract Background Social interactions can have a beneficial effect on people with dementia (PWD). However, little is known about the details of social interactions in dementia, information that is useful for planning social interventions. The aim of our study was to gain a deeper insight, provided by people in dementia care, into (i) the characteristics of social interactions of PWD, (ii) which social interactions are considered as particularly important, (iii) how important social interactions are perceived, and (iv) what is perceived to increase social interactions among PWD. Methods Responses of 501 people in dementia care (mostly family and professional caregivers; more than three-quarters female; average age 53.5 years) provided in a structured, quantitative survey were included in this analysis. Descriptive analyses were conducted. Results The majority of PWDs’ social interactions take place in their home or day care and arise from support services as well as organized activities. More than half of the participants perceived singing, telling life stories, or moving together (e.g., walking, dancing) as valuable social interactions that PWD benefit from in many ways. Positive effects (e.g., aggression, depression, positive emotions, activation) are mainly perceived for social interactions such as laughing together, touch, hugging, simply being together, or being involved in daily activities. Overall, participants rated social interactions as rather important for the course of the symptoms. A fixed social contact besides the primary caregiver and offers from the community, associations, and religious institutions are considered rather important in increasing the social interactions of PWD. Conclusions Simple social interactions of PWD such as laughing, eating or singing together that can be realized in the home environment and in the context of organized caregiving activities are perceived most valuable. Enhancing social interactions, especially beyond the primary caregiving context, may be valuable for those living with dementia.